Evaluation of flooding points in the Professional Sector of the University city Professor José da Silveira Netto (Research, Society and Development, 2020)
Studies on water pollution and urban floods are increasingly frequent, as they may be related to the expansion and urban population growth of large cities or to climate changes that may be causing the increasing in sea levels and consequently the intensification of the flooding potential in coastal regions, especially those located below sea level. Thus, these issues need to be studied for sustainable management of urban basins. The research aims to evaluate flooding points of the professional sector of the University City Professor José da Silveira Netto. For this purpose, the Digital Terrain Model-MDT of the study area was initially surveyed and then some altimetric levels that are directly influenced by the highest tides were evaluated. The tidal data were extracted from the Center for Weather Forecast and Climate Studies of the National Institute for Space Research-CPTEC-INPE (2020) in the city of Belém-PA. Then, the maximum height of high tide, precipitation and elevation levels were correlated, and it was found that in some areas of the professional sector with levels below the maximum elevation level regardless of precipitation, flooding occurs and thy intensify when the high tide and precipitations coincide. Flooding generally occurs with greater intensity in the first quarter of the year, which coincides with the highest precipitation and the highest tide heights. Some action must be taken by the campus administration in order to minimize the impacts of these floods.